Інтегровані корпоративні формування за участю м’ясопереробних підприємств - Соломчук, Людмила Миколаївна (My University, 2015)
Дисертаційна робота присвячена поглибленому дослідженню теоретичних та методичних особливостей створення інтегрованих корпоративних формувань за участю м’ясопереробних підприємств. The thesis is devoted to wide of in-depth theoretical and methodological features of integrated corporate formations involving meat processing enterprises. Theoretical approach in the direction of concepts and categories of integration was investigated, especially distinction of phenomenon of concept of «agricaltural ingration» and «corporation». Motives, reasons and necessity of integration in meat subcomplex were defermined.
Keywords: кафедра обліку і аудиту; м’ясопродуктовий підкомплекс; інтеграція; інтегровані корпоративні формування; meat subcomplex; integration; integrated corporate formation